Value of serum 1,5-anhydroglucitol measurements in childhood obesity in the continuum of diabetes - Ha Yeong Yoo; Byung Ok Kwak; Jae Sung Son; Kyo Sun Kim; Sochung Chung (Korean Society of Pediatric Endocrinology, 2015)
PurposeThe prevalence of type 2 diabetes mellitus (T2DM) and obesity are currently increasing. Accordingly, the concept of "preventing diabetes" in high-risk groups has become more important in diabetic care, but the use of glycated hemoglobin (HbA1c) as a measure has limitations in this field. The aim of this study was to investigate the utility of 1,5-anhydroglucitol (1,5-AG) in assessing prediabetes status in obese children.MethodsThe medical records of 74 subjects aged 6-19 years (of which 27 were overweight/obese and 47 had diabetes) who had 1,5-AG data were reviewed retrospectively. We compared 1,5-AG with HbA1c using the Pearson correlation test to assess the clinical utility of 1,5-AG.Results1,5-AG levels were higher (31.1±10.1 µg/mL vs. 7.4±7.3 µg/mL) and HbA1c levels were lower (5.5%±0.3% vs. 8.9%±2.7%) in the overweight/obese group than in the diabetics group. The range of 1,5-AG levels in obese children was wide (16.8-59.3 µg/mL), and did not have significance with HbA1c. A negative correlation between 1,5-AG and HbA1c was significant in the entire subject (r=-0.822, P<0.001), and also in the HbA1c range of 5.5% to 8% (r=-0.736, P<0.001).Conclusion1,5-AG is a valuable index in the HbA1c range of 5.5%-8% and it might be considered an early glycemic control index in insulin-resistant obese children with an HbA1c level above 5.5%. Moreover, the 1,5-AG level assessment should be presented as a supplementary tool for better compliance, as well as being an improvement in diabetes management for the short-term glucose control in relatively well-controlled diabetes patients with an HbA1c level below 8%.